A Comparative Study of Honey Dressing Vs Silver Sulfadiazine Dressing on Wound Healing in Burn Patients - Singh, Amritjot; Bajaj, Satinderjit Singh; Bajaj, Jagminder Kaur (British Journal of Healthcare and Medical Research, 2025)
Aim and Objectives: To compare the effects of honey vs silver sulfadiazine for wound healing in burn patients. Material and Methods: Study was conducted in 60 patients. 30 in each group i.e honey group and SSD group with age between 18-70 years . clinical assessment of wound encompassing the sight, affected BSA, degree, depth, absence/presence of slough and additional treatment was documented chronologically. Results: By the end of 6 weeks number of patients showing complete healing was significantly increased with honey dressing than SSD. Swab cultures to both the groups showed the prevalence of S.aureus, Pseudomonas and Klebsiella and treated with drugs like Fluroquinolones , Amoxicillin-clavulinic acid and Linezolid. Conclusion: Honey causes complete healing of wound faster than SSD and the mean percentage decrease in wound size is significant with Honey Dressing in 2nd and 4th week.